Recurrent mutation of JAK3 in T‐cell prolymphocytic leukemia. Issue 4 (21st January 2014) - Bergmann, Anke K.; Schneppenheim, Sina; Seifert, Marc; Betts, Matthew J.; Haake, Andrea; Lopez, Cristina; Maria Murga Penas, Eva; Vater, Inga; Jayne, Sandrine; Dyer, Martin J.S.; Schrappe, Martin; Dührsen, Ulrich; et al.
<x xml:space="preserve">Abstract</x> T‐cell prolymphocytic leukemia (T‐PLL) is an aggressive post‐thymic T‐cell malignancy characterized by the recurrent inv(14)(q11q32)/t(14;14)(q11;q32) or t(X;14)(q28;q11) leading to activation of either the TCL1 or MTCP1 gene, respectively. However, these primary genetic events are insufficient to drive leukemogenesis. Recently, activating mutations in JAK3 have been identified in other T‐cell malignancies. Since JAK3 is essential for T‐cell maturation, we analyzed a cohort of 32 T‐PLL patients for mutational hot spots in the JAK3 gene using a step‐wise screening approach. We identified 14 mutations in 11 of 32 patients (34%). The most frequently detected mutation in our cohort was M511I (seen in 57% of cases) previously described as an activating change in other T‐cell malignancies. Three patients carried two mutations in JAK3. In two patients M511I and R657Q were simultaneously detected and in another patient V674F and V678L. In the latter case we could demonstrate that the mutations were on the same allele in cis. Protein modeling and homology analyses of mutations present in other members of the JAK family suggested that these mutations likely activate JAK3, possibly by disrupting the activation loop and the interface between N and C lobes, increasing the accessibility of the catalytic loop. In addition, four of the 21 patients lacking a JAK3 point mutation presented an aberrant karyotype involving the chromosomal band 19p13 harboring the JAK3 locus. The finding of recurrent activating JAK3 mutations in patients with T‐PLL could enable the use of JAK3 inhibitors to treat patients with this unfavorable malignancy who otherwise have a very poor prognosis. © 2014 Wiley Periodicals, Inc.